Rapid and efficient sequestration of arsenic from contaminated water using hypertolerant Bacillus L-148 sp.: a two-step process - Bagade, Aditi; Nandre, Vinod; Ghosh, Sayanti; Battu, Shateesh; Haram, Santosh; Giri, Ashok; Kodam, Kisan (Green Chemistry, 2019)
A fast, robust and green bioreactor for arsenic sequestration from contaminated water was designed. In the two-tier bioreactor, bacterial arsenite detoxification (1 mM) was carried out followed by precipitation of arsenate in 5 min. The precipitate could be used for supercapacitor applications. This bioreactor yielded arsenic free water, therefore, this method can be adopted for scale-up. The combination of hypertolerant bacteria and fast precipitation indicates the robustness of this pilot bioreactor.